El acceso al crédito formal argentino en tiempos de crisis: Un análisis a partir del impacto del Covid-19 con perspectiva de género - Laura Cuccaro (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2023)
– Covid-19 has led to worse economic consequences for women and deepened the structural problems to reach their economic autonomy. This document provides empirical evidence for Argentina regarding access to credit by gender during the pandemic outbreak. The results show that although credit declined for both men and women, the fall was deeper for the latter. Credit cards were a crucial credit resource. The lower relative access of women to finance through this instrument may have prompted the search for non-banking financing, worsening their credit financial conditions compared to men. Additionally, the study provides new evidence to the literature that stands by the idea that households with lower income and higher care demand were more vulnerable to the Crovid-19 crisis.
Keywords: 330; Kreditgeschäft; Kreditwürdigkeit; Verbraucherkredit; Kreditkarte; Frauen; Coronavirus; Argentinien